Penyuluhan dan Pemeriksaan Mata Pekerja Tambak di Kabupaten Sidoarjo, Jawa Timur - Noviani Prasetyaningsih; Gita Handayani Tarigan; Anggraeni Adiwardhani; Jihan Samira Tsabit (CV. Multi Kreasi Media, 2025)
Background: Ultraviolet (UV) rays from the sun can have harmful effects that lead to decreased visual acuity in humans. The most dangerous UV exposure occurs between 10 a.m. and 4 p.m. Fishpond workers spend almost the entire day working under direct sunlight. Low awareness and lack of concern for eye health further increase the adverse effects of UV rays. We conducted a community service program for fishpond workers in Sidoarjo Regency, East Java. Methods: We provided education on the dangers of UV radiation and conducted eye examinations for 69 fishpond workers. Results: The respondents consisted of 69 individuals, including 54 males (78,26%) and 15 females (21,74%). The age distribution was 62,32% aged 36–50 years, 23,19% over 50 years, and the remaining were 20–35 years old. Among them, 59.42% worked under direct sunlight for 3–5 hours, and 57.97% were smokers. Knowledge about UV hazards significantly improved after the education session, from 36,23% to 79,71%. Eye diseases identified included 30.43% cataracts, 78.26% dry eye disease, and 7.25% pterygium. Conclusion: Regular education and eye examinations for fishpond workers are necessary to maintain better eye health.